SINERGITAS PEREMPUAN (Studi Paradigmatis Yusuf Qardhawi dalam Fatawa Al-Mu’āshirah) - Nahdliyyatul - Azimah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
The synergy of women in various sector of life is explained directly by Yusuf al-Qardhawi in the Fatawa Al-Mu'āshirah. He is a contemporary fiqh scholar, his work has been widely reviewed by academics and is used as a reference at formal and non-formal institutions. Her moderate and loose attitude in looking at women's affairs attracted writers to examine her paradigm. This research is classified as descriptive-qualitative. Data analysis was carried out through an in-depth study of volume three of the book Fatawa Al-Mu'āshirah and the results were discussed with the author's partners. The results are: 1) Since Adam as., there is has been a contribution of women, namely Hawa. 2) Since of the history of Islam, there is contribution of women has been prominent in family realm, da’wah of Islam, thought, education, literature, politics, science, economy, social and culture. 3) The role of muslimah at various sector of life needs to be improved, which society really needs.